BATYRBAY SECTION, SOUTH KAZAKHSTAN, U.S.S.R. - POTENTIAL STRATOTYPE FOR THE CAMBRIAN–ORDOVICIAN BOUNDARY - Dubinina S.V.; Apollonov M.K.; Zhemchuzhnikov V.G.; Chugaeva M.N. (My University, 1988)
The base of the Cordylodus proavus conodont Zone is the most appropriate horizon for the Cambrian–Ordovician Boundary. At Batyrbay the horizon reflects a significant global eustatic event that is marked by distinctive geochemical changes and by drastic changes in the trilobite and conodont faunas. The palaeomagnetic polarities change from reversal to normal just below this horizon.
Keywords: Ordovician; Cambrian; Палеозой::Ордовикская; Paleozoic::Cambrian; Paleozoic::Ordovician; Палеозой::Кембрийская